2022
DOI: 10.1136/jmedgenet-2022-108485
|View full text |Cite
|
Sign up to set email alerts
|

Targeted long-read sequencing identifies missing pathogenic variants in unsolved Werner syndrome cases

Abstract: BackgroundWerner syndrome (WS) is an autosomal recessive progeroid syndrome caused by variants in WRN. The International Registry of Werner Syndrome has identified biallelic pathogenic variants in 179/188 cases of classical WS. In the remaining nine cases, only one heterozygous pathogenic variant has been identified.MethodsTargeted long-read sequencing (T-LRS) on an Oxford Nanopore platform was used to search for a second pathogenic variant in WRN. Previously, T-LRS was successfully used to identify missing va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Although additional read depth would be required to confidently assess the parent of origin of the duplicated allele, we have demonstrated that methylated reads can be phased such that parent-of-origin could be determined in samples with sufficient depth. Parent-of-origin for this variant has potential prognostic implications because individuals with 15q11.2-q13 duplications of the paternal allele typically develop less severe autism spectrum disorder than individuals with duplications of the maternal allele [ 25 ]. In the case we presented, we relied on a single nearby SNV to phase reads.…”
Section: Discussionmentioning
confidence: 99%
“…Although additional read depth would be required to confidently assess the parent of origin of the duplicated allele, we have demonstrated that methylated reads can be phased such that parent-of-origin could be determined in samples with sufficient depth. Parent-of-origin for this variant has potential prognostic implications because individuals with 15q11.2-q13 duplications of the paternal allele typically develop less severe autism spectrum disorder than individuals with duplications of the maternal allele [ 25 ]. In the case we presented, we relied on a single nearby SNV to phase reads.…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly true in the case of genomic disorders, a term first coined by Lupski in 1998 to describe diseases that result from rearrangements of the human genome rather than from DNA sequence base changes 10 . There are indeed a few studies demonstrating the superiority of LRS over SRS in this class of disorders 11,12 . However, whole genome LRS is still prohibitively expensive for routine genetic diagnosis and remains largely inaccessible due to complex workflow and stringent sample requirement for ultrahigh molecular weight DNA.…”
Section: Mainmentioning
confidence: 99%
“…Research studies over the last several years have highlighted the utility of long reads in diagnosing genetic disorders where the standard of care assays fail to achieve a molecular diagnosis (Amarasinghe et al, 2020;Ardui et al, 2018;Borras et al, 2017;Melas et al, 2022;D. E. Miller et al, 2021D. E. Miller et al, , 2022.…”
Section: Long-read Sequencing (Lrs)mentioning
confidence: 99%
“…Research studies over the last several years have highlighted the utility of long reads in diagnosing genetic disorders where the standard of care assays fail to achieve a molecular diagnosis (Amarasinghe et al, 2020; Ardui et al, 2018; Borras et al, 2017; Melas et al, 2022; D. E. Miller et al, 2021, 2022). These studies fall into the two broad categories: (1) identifying pathogenic variants in regions difficult to sequence with short‐reads: repeat expansions, homopolymers, protein‐coding genes with pseudogenes, long insertions (>50 base pairs), and complex structural rearrangements, and (2) resolving unknown or uncertain phase in autosomal recessive conditions where short‐read technology requires additional sequencing of parental samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation